Adoption of the kanban process for the proper functioning of the cutting section in a selected apparel manufacturing plant - Niroshan, T.S. (University of Jaffna, 2020)
In the Apparel Industry, the cutting section serves an important role in the manufacturing process. It deals directly with Raw Materials stores and the Production floor. This particular department has the responsibility to maintain a proper coordination between their suppliers(Raw Materials Stores) and Customers (Production floor). The major intention of this project was to initiate the application of Kanban process for the proper material flow throughout the selected apparel plant as material flow plays a significant part in determining the inventory control and waste minimization. For this particular study, the relevant data were gathered from the cutting section over a specific period, and the mapping of the material flow with defining the responsibilities of each department were carried out. It was followed by the preparation of the Kanban cards and the direction of its movement was clearly specified while the results were examined over few weeks in terms of Material requisition note and the downtime analysis. The expected outcomes were reached over the long run of the implemented activity. Proper formulation of the activity provided a visual identification in the cutting section with a clear glance of duties and responsibilities.
Keywords: Apparel industry; Cutting section; Kanban process; Inventory control; Material requisition note; Downtime analysis